1999
DOI: 10.1001/archsurg.134.7.699
|View full text |Cite
|
Sign up to set email alerts
|

Reoperative Parathyroid Surgery in the Era of Sestamibi Scanning and Intraoperative Parathyroid Hormone Monitoring

Abstract: Hypothesis: Results of reoperative parathyroid surgery (RPS) have improved with the advent of sestamibi parathyroid subtraction scanning and intraoperative parathyroid hormone (IOPTH) monitoring. Design: Retrospective review of patient histories, preoperative localization studies, operative data, including IOPTH monitoring, and outcomes for patients undergoing recent RPS at a single institution. Follow-up was complete (mean, 20 months). Setting: Tertiary care referral center. Patients: All patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 13 publications
(15 reference statements)
2
77
0
5
Order By: Relevance
“…Use of preexcision samples has been suggested to reduce the number of false-negative results in patients with a single adenoma (33,42 ). Timing of postexcision samples is generally at 5 and/or 10 min, although timings of 7 and 20 min have been used in reported studies (44,45 ). A recent protocol has suggested that an immediate post-gland excision sample may also be useful (46 ).…”
Section: Interpretation Of Rapid Intraoperative Pth Assay Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of preexcision samples has been suggested to reduce the number of false-negative results in patients with a single adenoma (33,42 ). Timing of postexcision samples is generally at 5 and/or 10 min, although timings of 7 and 20 min have been used in reported studies (44,45 ). A recent protocol has suggested that an immediate post-gland excision sample may also be useful (46 ).…”
Section: Interpretation Of Rapid Intraoperative Pth Assay Resultsmentioning
confidence: 99%
“…Cure rates of Ͼ95% have been reported in several studies (7,29,32,49,50 ), including one study with up to 5 years of follow-up (51 ). In addition, the rapid PTH assay has been shown to be useful in cases of secondary-tertiary hyperparathyroidism (32,39,52 ), as well as in reoperative cases for failed surgery or recurrent disease (32,45,53,54 ). The assay has also been reported to predict severe postoperative hypocalcemia in reoperative patients with multiglandular disease (55 ).…”
Section: Clinical Utility Of Rapid Intraoperative Pth Testsmentioning
confidence: 99%
“…9 Thompson et al recently reported an 88% cure rate at reoperation, with a 13% rate of Hypocalcemia and a 0.8% incidence of nerve injury. 11 In interpreting reoperative results, we must remember that the hypoparathyroidism is most likely secondary to injury or removal of normal parathyroid glands at the initial procedure rather than to injury to normal glands at reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Thompson et al (1999) suggested that a cut-off of 70% would result in the identification of a higher proportion of patients with multiglandular disease. On the other hand, Dackiw et al (2000) proposed that, when using the ioPTHi determination in patients with MEN1, it is reasonable to apply the same target used by Clary et al (1997) -an approximately 80% decrease in ioPTHi level-in patients with secondary hyperparathyroidism and parathyroid hyperplasia.…”
Section: Radio-guided Surgery and Intraoperative Ipth Determination Imentioning
confidence: 99%